2018
DOI: 10.1371/journal.pone.0199866
|View full text |Cite
|
Sign up to set email alerts
|

Genetics instability of wtAAV2 genome and AAV promoter activities in the Baculovirus/Sf9 cells system

Abstract: The human Adeno-Associated Virus serotype 2 (wtAAV2) is a common non-pathological virus and its recombinant form (rAAV) is widely used as gene therapy vector. Although rAAVs are routinely produced in the Baculovirus/Sf9 cell system, wtAAV2 has never been studied in this context. We tried to produce wtAAV2 in the baculovirus/Sf9 cell system hypothesizing that the wtAAV2 may be considered as a normal recombinant AAV transgene. Through our attempts to produce wtAAV2 in Baculovirus/Sf9, we found that wtAAV2 p5 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…By comparing several rAAV serotypes we were able to demonstrate that another supplementary band (slightly smaller than the VP1 protein) was not a degradation product of the VP1 protein but originated from internal translation initiation in codon optimized cap sequences. Interestingly, we have previously shown that rep gene codon optimization could lead to supplementary transcription events compared to a non-optimized rep gene construct [ 31 ]. Thus codon optimization of AAV genes in the context of baculovirus expression system should be carefully checked and compared to non-optimized genes.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing several rAAV serotypes we were able to demonstrate that another supplementary band (slightly smaller than the VP1 protein) was not a degradation product of the VP1 protein but originated from internal translation initiation in codon optimized cap sequences. Interestingly, we have previously shown that rep gene codon optimization could lead to supplementary transcription events compared to a non-optimized rep gene construct [ 31 ]. Thus codon optimization of AAV genes in the context of baculovirus expression system should be carefully checked and compared to non-optimized genes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the Two-Bac system, Smith et al [35] A more recent modification utilized the weak initiation codon for Rep78, which enabled partial exon skipping and subsequent expression of downstream Rep52 from a single expression cassette and reportedly enhanced Bac-Rep stability for at least five passages. [41] In the Mono-Bac, [37] the rep-cap expression cassette reported in Two-Bac [35] was integrated into the egt (ecdysteroid UDP- Rep proteins was also critical to avoid Rep-induced excision of AAV expression cassette [42] and its integration stability in baculovirus genome as this can ultimately affect the stability of Mono-Bac BEV and overall production titer of AAV vectors.…”
Section: Enhancement In Aav Rep Expressionmentioning
confidence: 99%
“…The very late phase expression of Rep proteins, specifically after baculovirus DNA replication, minimized Rep‐induced excision of the rep‐cap expression cassette from the baculovirus genome, resulting in sustained expression stability. Furthermore, this late phase expression of Rep proteins was also critical to avoid Rep‐induced excision of AAV expression cassette [ 42 ] and its integration stability in baculovirus genome as this can ultimately affect the stability of Mono‐Bac BEV and overall production titer of AAV vectors.…”
Section: Molecular Design Of Baculovirus Expression Vectors and Cell mentioning
confidence: 99%
“…Although expression platforms are usually trade secrets, most rAAV production systems use a variety of co-infecting AAV helper viruses. The adenoviral system has been developed and improved in terms of safety by using only essential sets of “early” adenovirus genes (e.g., E1, E2, E4, and VA RNA I and II), expressed from plasmid, without the lytic “late” genes [ 15 , 16 , 17 , 18 ]. In this set-up, the E1 gene is generally supplied by a producer cell line (HEK293, PER.C6, Hela-E1).…”
Section: Introductionmentioning
confidence: 99%
“…This system uses three baculoviruses to collocate into the Sf9 cell the AAV rep and cap genes along with the rAAV transgene [ 17 ]. A significant problem with this early work was the inability of the Sf9 cell to recognize the splicing signal used by AAV [ 18 ]. This meant that the regulation of VP1-VP2-VP3 ratios was solely achieved through a ribosome scanning mechanism, linked to the use of non-ATG initiation codons.…”
Section: Introductionmentioning
confidence: 99%